A new versatile constitutive law for modelling the monotonic response of soft rocks and structured fine‐grained soils. (29th July 2019) - Boldini, Daniela; Palmieri, Francesca; Amorosi, Angelo
Summary: This paper deals with a new critical state–based constitutive model for soft rocks and fine‐grained soils. The model, formulated in the single‐surface plasticity framework, is characterised by the following main features: (i) a generalised three‐invariant yield surface capable of reproducing a wide set of well‐known criteria, (ii) the dependency of the elastic stiffness on the current stress state by means of a hyperelastic formulation, (iii) the ability of simulating the plastic strain–driven structure degradation processes by a set of appropriate isotropic hardening laws, and (iv) a nonassociate flow rule in the meridian plane. The adopted formulation is hierarchical, such that the various features of the model can be activated or excluded depending on the specific kind of geomaterial to be modelled and on the quality and quantity of the related available experimental results. The constitutive model was implemented in a commercial finite element code by means of an explicit modified Euler scheme with automatic substepping and error control. The procedure does not require any form of stress correction to prevent drift from the yield surface. The performance of the model is first analysed by means of a wide set of parametric analyses, in order to highlight the main features and to evaluate the sensitivity of the formulation with reference to the input parameters. The model is then adopted to simulate the experimental response observed on three different geomaterials, ranging from soft clays to soft rocks.